MANAJEMEN DAN SISTEM PENDUKUNG BIMBINGAN DI SD GMIT 07 KABOLA - Miseri Kordia Lau; Adesti Asmarita Kamba, Asarina Alomalai, Beci Selfina Oko, Yessy Mata, Petrus Mau Tellu Dony, Yeremi (CV. Adiba Aisha Amira, 2025)
This study aims to describe the guidance management and support system at GMIT 007 KABOLA Elementary School in an effort to support optimal student development. Guidance in elementary schools plays a crucial role in character formation, increasing learning motivation, and helping students overcome academic and socio-emotional difficulties. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that guidance management at GMIT 007 KABOLA Elementary School has been implemented in a structured manner through a guidance planning program, character and learning training activities, and ongoing evaluation. The mentoring system includes the involvement of the principal, class teachers, parents, and local community leaders. However, challenges remain in terms of limited specialized guidance experts and supporting facilities. Therefore, increased teacher training in guidance services and collaboration with external parties are needed to support the effectiveness of the guidance program. These findings have significant implications for the development of holistic and contextual guidance management at the elementary school level.